1 - CODESRIA: 30 years of Scholarly Publishing - Adebayo Olukoshi; Francis B. Nyamnjoh (Africa Media Review, 2006)
In this essay, the authors examine the role of CODESRIA in African knowledge production and distribution since its founding some three decades ago. The authors also discuss the motivation for the creation of CODESRIA, as well as the challenges, achievements, and promises of this pan African research organization in developing a culture of scholarly publishing and dissemination in the continent.